2018
DOI: 10.1002/alr.22168
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐induced respiratory symptoms improve after aspirin desensitization in patients with aspirin‐exacerbated respiratory disease

Abstract: The majority of patients with AERD who experience respiratory symptoms with alcohol consumption describe improvement in this domain following aspirin desensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…Consistent with multiple single‐arm observational studies (which some might classify as case‐series in design) reporting a qualitative benefit of aspirin in AERD, we quantified these to be a mean MD 10.27 better in SNOT‐22 QoL (RR 2.00 [95% CI, 1.31 to 3.06]; absolute risk (AR) 48% [95% CI, 31% to 73%]; number needed to treat [NNT] 5 [95% CI, 3 to 14]), and MD 2.56 better in AAO nasal symptoms (RR 2.20 [95% CI, 1.55 to 2.73]; AR 66% [95% CI, 47% to 82%]; NNT 3 [95% CI, 2 to 7]). Additional reported benefits of aspirin desensitization include reduced nasal polyp recurrence, improved olfaction, improved alcohol tolerance, and decreased use of intranasal and oral corticosteroids . It is important to note that these findings were from long‐term investigations up to 6 years of follow‐up.…”
Section: Discussionmentioning
confidence: 87%
“…Consistent with multiple single‐arm observational studies (which some might classify as case‐series in design) reporting a qualitative benefit of aspirin in AERD, we quantified these to be a mean MD 10.27 better in SNOT‐22 QoL (RR 2.00 [95% CI, 1.31 to 3.06]; absolute risk (AR) 48% [95% CI, 31% to 73%]; number needed to treat [NNT] 5 [95% CI, 3 to 14]), and MD 2.56 better in AAO nasal symptoms (RR 2.20 [95% CI, 1.55 to 2.73]; AR 66% [95% CI, 47% to 82%]; NNT 3 [95% CI, 2 to 7]). Additional reported benefits of aspirin desensitization include reduced nasal polyp recurrence, improved olfaction, improved alcohol tolerance, and decreased use of intranasal and oral corticosteroids . It is important to note that these findings were from long‐term investigations up to 6 years of follow‐up.…”
Section: Discussionmentioning
confidence: 87%
“…[9][10][11] Oral aspirin desensitization (AD) has been shown to be an effective tool for disease control. 3,[10][11][12] More recently, studies have shown that sinus surgery followed by AD and maintenance therapy leads to effective long-term control of sinus disease burden in AERD. 7,13,14 Despite the efficacy of corticosteroids in the treatment of AERD, little is known regarding the impact upon corticosteroid use of surgical treatment of inflammatory burden followed by AD.…”
mentioning
confidence: 99%
“…18 In addition to steroid rinses, postoperative aspirin desensitization further improves outcomes in patient-reported QOL, alcohol tolerance, olfaction, and endoscopy scores, resulting in contemporary revision surgery rates as low as 9% at 30 months. 6,19,20 There is no question that despite all of the above interventions, polyps do recur in some AERD patients, resulting in impaired QOL and worse control of CRS. 21 The advent of biologics promises to revolutionize the treatment of these patients who would otherwise be subjected to chronic systemic steroid use.…”
Section: How To Cite This Article Schlosser Rodney J Aspirin-exacerbamentioning
confidence: 99%
“…Alcohol sensitivity may be present in up to 75% of AERD patients. 1,6 Reports have differed on the association of atopy with AERD, with some authors suggesting there is no increase compared to non-AERD patients, whereas others report atopy rates as high as 82% in AERD patients. 2,7 Two additional clinical factors that are of particular interest to rhinologists are the impact of AERD upon olfaction and the unique distribution of polyps on computed tomography (CT).…”
mentioning
confidence: 99%